1994
DOI: 10.1002/hep.1840190306
|View full text |Cite
|
Sign up to set email alerts
|

“Inapparent” hepatitis B virus infection and hepatitis C virus replication in alcoholic subjects with and without liver disease

Abstract: We evaluated hepatitis B virus DNA and hepatitis C virus RNA in sera from 110 HBsAg and IgM HBc antibody-negative heavy drinkers (50 cirrhosis, 13 chronic active hepatitis, 25 fatty liver with or without mild to moderate fibrosis, alcoholic hepatitis or both and 22 healthy alcoholic subjects) with polymerase chain reaction. Results of hepatitis C virus polymerase chain reaction were compared with those obtained with two tests (second generation recombinant immunoblot assay and enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 30 publications
2
13
1
1
Order By: Relevance
“…In this study, occult HBV infection was not observed in the evaluated patients, and these results are in accordance with those found by ZIGNEGO et al (5) who showed that occult HBV infection is rare in Italian HBsAg-negative alcoholic patients. These same results, however, are different from those found by NALPAS et al (3) who reported a high percentage of serum positive HBV DNA in alcoholics who were negative for HBsAg and even in some who had none of the usual HBV infection markers.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, occult HBV infection was not observed in the evaluated patients, and these results are in accordance with those found by ZIGNEGO et al (5) who showed that occult HBV infection is rare in Italian HBsAg-negative alcoholic patients. These same results, however, are different from those found by NALPAS et al (3) who reported a high percentage of serum positive HBV DNA in alcoholics who were negative for HBsAg and even in some who had none of the usual HBV infection markers.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, serum markers for HCV infection have been detected in 33% to 50% of alcoholic patients with evidence of liver injury, compared to only 2% to 10% in those without any sign of liver disease (4,5,7,10,13,15,21,23,24,25,26,27,30,33,35) . In the present study, anti-HCV antibodies were detected in 17 (15%) of 114 unselected alcoholic patients admitted to our detoxifi cation unit.…”
Section: Discussionmentioning
confidence: 99%
“…60 Therefore, in patients with severe acquired im- 2). HCV infection has been associated with severe liver dis- 14:195-199. ease in many studies; [76][77][78][79] …”
Section: General Population and Blood Donorsmentioning
confidence: 99%